Christianity in the early centuries - Evangelical Theological Society. Meeting (2005) (Valley Forge, Penn. : Acts Conference Products, 2005)
Each CD-ROM includes table of contents in a .pdf file and audio of various speakers discussing Biblical topics.
v.2 disc 4. Near East archaeology society: Archaeology of the early centuries of Christianity ; General session ; Special session in honor of Edwin M. Yamauchi -- Evangelical philosophical society I ; Evangelical philosophical society II -- Open sessions: Apologetics -- Study groups: Asia minor ; Jonathan Edwards ; New projects in systematic theology ; Other voices of Biblical interpretation ; Patristics ; Spiritual formation ; Synoptic gospels ; Young scholars group ; Wesleyan studies -- disc 5. Open sessions: Church history and historical theology ; Apologists ; Apostolic fathers ; Augustine I ; Augustine II ; Calvinism ; Christianity in Alexandria ; Church history and the early church ; Early centuries ; Early church ; Early church in North Africa ; Gender issues ; Gnostics and gnostic gospels ; Historical Theology: 18th - 20th centuries ; Jonathan Edwards ; Medieval and reformation ; Missions to Asia ; Nicea and Arianism ; Origen and Cyril of Alexandria -- disc 6. Open sessions: Church history and historical theology (continued from disc 5): Renaissance and reformation ; Spiritual formation ; Spirituality ; Walter Bauer's thesis.
"November 16018, 2005 - Valley Forge, PA" -- on discs.
MP3 audio plays in Windows Media Player (PC), Quicktime (Mac) or any MP3 player.
Keywords: Bible -- Evidences, authority, etc; Christianity; Theology; Bible as literature